Growth Performances, Carcass and Organs Characteristics and Economics Results of Growing Indigenous Senegal Chickens Fed Diets Containing Various Levels of Leuceana leucocephala (Lam.) Leaves Meal - Ayssiwede, S.B.; Chrysostome, C.A.A.M.; Zanmenou, J.C.; Dieng, A.; Houinato, M.R.; Dahouda, M.; Akpo, Y.; Hornick, J.L.; Missohou, A. (International Journal of Poultry Science, 2011)
The aim of this study carried out from September to December 2010 was to evaluate the effects of Leuceana leucocephala leaves meal inclusion in the diets on growth performances, carcass and organs characteristics and economics results of growing indigenous Senegal chickens. One hundred and four (104) indigenous Senegal chicks of 4 weeks old were randomly allocated into four groups of 26 chicks each with similar body weight. Each group subdivided in two repetitions of 13 birds, corresponded to each of the four (4) dietary treatments LL0, LL7, LL14 and LL21 containing respectively 0, 7, 14 and 21% of Leuceana leaves meal in substitution of groundnut cake meal. During the experiment (5-17th week old), zootechnical parameters of birds and economical data were recorded and analyzed per dietary treatment. At the end of the 13 weeks trial, the final Live Body Weights (LBW) were 864 g, 1166.48 g, 905 g and 887.16 g/bird, the Average Daily Weight Gain (ADWG) were 7.77 g, 10.88 g, 8.15 g and 8.10 g/day, the Daily Feed Intake (DFI) of 39.86 g, 51 g, 40.39 g and 44.75 g/bird and the Feed Conversion Ratio (FCR) of 7.04, 5.54, 6.27 and 6.80 respectively for birds fed LL0, LL7, LL14 and LL21 diets. The Leuceana leaves meal inclusion in the diets up to 21% had not caused any adverse effect on LBW, ADWG, DFI, FCR, mortality, carcass and organs characteristics in birds compared to their controls. Apart from the dark yellowing of abdominal fat of carcasses from birds fed LL21 diet, significantly better growth performances, feed costs and economic margins were recorded in birds fed LL7 and LL14 diets. Thus, these two dietary treatments were the only most economically profitable (respectively 214 and 48 FCFA/kg carcass of additional profit) compared to the control.